Analisis Kesalahan Penggunaan Possessivpronomen dalam Kalimat Sederhana Bahasa Jerman - Reza Pratama Putra; Ambo Dalle (Universitas Negeri Makassar, 2023)
Abstract. The purpose of this study was to obtain data about errors in the use of Possessivpronomen for class XI students of SMA Negeri 8 Makassar. This research is a type of descriptive research with a quantitative method approach. The population of this study were students of class XI SMA Negeri 8 Makassar consisting of 184 students. The research sample was Class XI MIPA 4 as an experimental class consisting of 36 students. Research data were analyzed using written tests and open questionnaires. Based on the results of the research data analysis, it was shown that the highest number of errors made by students were in simple Possessivpronomen sentences with Akkusativ cases for Masculine types of 19 students out of 36 students and in Possessivpronomen usage errors with Nominativ cases for Masculine and Feminine types by 15 out of 36 studentsKeyword: Error analysis, Possessivpronomen simple sentences, German